Knock-Down of Specific Thyroid Hormone Receptor Isoforms Impairs Body Plan Development in Zebrafish - Lazcano, Iván; Rodríguez-Ortiz, Roberto; Villalobos, Patricia; Martínez-Torres, Ataúlfo; Solís-Saínz, Juan Carlos; Orozco, Aurea (Frontiers in Endocrinology, 2019)
The role of thyroid hormones (THs) in development has been extensively studied, however, the specific molecular mechanisms involved are far from being clear. THs act by binding to TH nuclear receptors (TR) that act as ligand-dependent transcription factors to regulate TH-dependent gene expression. Like vertebrates, zebrafish express different isoforms of functional Tr alpha and beta, some of which can bind alternative ligands like 3,5-T2. In this study, we first analyzed the effects of exogenous T3 and 3,5-T2 exposure during embryogenesis. The percentage of affected embryos was similar to those vehicle-injected, suggesting that the early exposure to low TH levels is not sufficient to elicit effects upon the phenotype of the embryo. We then generated crispants for four isoforms of thr to learn more about the role of these receptors in early development. We found that crispant larvae from thraa and a newly identified l-thrb+, but not thrab and canonical thrb1 showed profound deleterious effects upon symmetry and laterality, suggesting early novel roles for these Tr isoforms in the body plan developmental program. Since critical events that determine cell fate start in the late gastrula, we tested if some genes that are expressed during early developmental stages could indeed be TH targets. We identify early development genes, like sox10 and eve, that were specifically over-expressed in thraa and l-thrb+ crispants, suggesting that these specific thr isoforms function as transcription repressors for these genes, while transcription of zic and ets appear to be thraa and l-thrb+-mediated, respectively. Overall, present results show that TH signaling participates in early zebrafish development and identify Tr isoform-specific mediated regulation of early gene expression.